Treating Functional Constipation (Liver Depression and Spleen Deficiency Type) based on the Theory of Qi Movement - Chen, Yanrong; Li, Changlin; Sun, Linmei (Journal of Contemporary Medical Practice, 2025)
Functional constipation (FC) is a clinically common intestinal disorder. Due to rapid societal development, an increasingly accelerated pace of life, continuous changes in lifestyle, heightened life stress, and alterations in dietary structure, the prevalence of FC has significantly increased in recent years. Although FC involves no organic pathologies related to the pelvic floor or intestines, it significantly and negatively impacts patients’ quality of life. Clinical studies indicate that FC patients often experience emotional states such as anxiety and depression [1]. Among FC patients, the pattern of Liver Depression and Spleen Deficiency is predominant. Traditional Chinese Medicine (TCM) demonstrates definite efficacy in treating FC. By regulating and smoothing Qi movement to fortify the spleen and harmonize the stomach, as well as soothe the liver and move Qi, TCM treatment harmonizes the Qi movement of the viscera, leading to smooth defecation. TCM treatment for FC holds a promising future.